Регулирование энергосистем при импульсных возмущениях - Иванов, И.Л. (Электронное моделирование, 2014)
Для модели энергосистемы с импульсным воздействием и запаздывающим регулированием численно найдены оценки области асимптотической устойчивости в пространстве управляющих параметров с помощью разрывных матричных функций Ляпунова двух типов и условий Разумихина. Для моделі енергосистеми з імпульсною дією та керуванням з запізненням чисельно знайдено оцінки області асимптотичної стійкості в просторі керуючих параметрів за допомогою розривних матричних функцій Ляпунова двох типів та за умов Разуміхіна. Estimations of the region of asymptotic stability in the space of control parameters are found for a power systemmodelwith pulse effects and delayed control by applying Lyapunov discontinuousmatrix functions and Razumikhin conditions. The piecewise exponential and piecewise linear functions were used as Lyapunov functions. Numerical estimations of stability regions in the space of control parameters were obtained by using each of these two types of Lyapunov functions. A comparison of the effectiveness of these two types of functions has been performed. The mechanisms of losing stability by the power system while varying its parameters are described.